Evaluation on vehicles emission productions in Iskandar Malaysia region towards Low Carbon society - Mohd. Safwan, Wan (Centre Environment Social & Economic Research (CESER), 2015)
The emission productions in Iskandar Malaysia from road transport-based are expected to increase about 14.26% in 2025 from 1.126million metric tons of current emission production as calculated in 2012. Iskandar Malaysia region has to take challenges to reduce about 4.7t-CO2 from its current emission productions towards achieving Low Carbon society in 2025 as road transport contributes about 27% from total emission productions. This paper provides some empirical findings and analysis based on annual population growth rates, vehicle ownerships and fuel consumptions pattern using Business as Usual (BAU) and selected Based on Scenario (BOS) methods for emission projections in the region